Breast Cancer Risk Reduction and Early Detection - Sauter, Edward R.; Daly, Mary B. (Springer US, 2010)
Breast Cancer Risk Reduction and Early Detection provides an in-depth overview of the factors of breast cancer risk and what health care providers and individuals can do to impact the risk of breast cancer in their patient or themselves. Many books address breast cancer in general or focus on treatment; few focus on prevention and early detection, including current practices and new strategies in: epidemiology, primary prevention, chemoprevention, surgical prevention, breast specific (physical examination, imaging, intraductal) and systemic screening and early detection. Written by experts in their fields, this book is a resource to researchers, clinicians and the broad group of health care providers. It is a source of accurate information for individuals to use to reduce risk of new or recurrent breast cancer and to apply best practices for early detection.